Parasitic zoonoses present some risks with low-temperature cooking of pork. (September 2016) - Purslow, Peter
Abstract: A recent article in this journal documents enhanced sensory qualities of pork cooked to low temperatures. The aim of this letter is to point out that the incidence of Trichinella spiralis in many countries and the more widespread incidence of Toxoplasma gondii present a concern for the adoption of low temperature cooking of pork unless extended cooking times are used.